AB0827 Painful Periprosthetic Resorption of Total Hip Arthroplasty Treated with Risedronate: an Observational Study. (10th June 2014) - Behra-Marsac, A.; Bonnet, C.; Mabit, C.; Coste, C.; Preux, P.-M.; Vergne-Salle, P.; Dufauret-Lombard, C.; Trèves, R.; Bertin, P.
Abstract : Background: Total hip arthroplasty (THA) is the treatment for severe hip osteoarthritis. It improves the quality of life, pain and patient autonomy. However, a periprosthetic resorption may occur, in 3% to 5% of patients after 10 years of the primary surgery requiring implant replacement. Bisphosphonates (BP), inhibitors of bone resorption, represent a potential candidate for modulating periprosthetic bone loss. Randomized controlled trials have also suggested that BP could prevent early periprosthetic bone loss after THA. Objectives: The aim of our study was to investigate the effect of a BP, risedronate on painful periprosthetic resorption in patients with THA, mainly on pain, radiographic bone loss, and periprosthetic density. Methods: A monocentric, longitudinal, observational study, cohort type, included patients with painful aseptic loosening of their THA, as defined by their surgeon. All patients received Risedronate 75mg, twice a month, during 2 years. The follow-up was made by the surgeon and the rheumatologist. Primary end point was walking pain measure by Visual Analogic Scale (VAS). Secondary measures included pain at rest, night pain, walking distance, number of surgical replacement of THA. THA X-Rays were analysed by a radiologist with O'Neill and Harris Criteria. Radiographic bone lesions were separated in 7 Gruen femoral area, and 3 Lee acetabular area. Periprosthetic bone mineral density of the femur was measured with DEXA (Dual Energy X-ray Absorptiometry) (Lunar iDXA) in 7 regions of interest defined according to the protocol of Gruen. All these measures were realized every 6 months. Results: 29 patients were included, mean age: 70 years. The mean period of first surgery of THA was 10, 7 years. At the inclusion, the mean walking pain, measured with VAS, was 4, 9. A statistically significant decrease of walking pain was observed 18 months after treatment (mean VAS: 2, 4). The walking distance has increase significativelly by 0, 95 km after 18 months. Concerning pain at rest, risédronate appears to provide improvements but because of the non-significance of the results, it cannot be confirmed. During the study, 8 patients required surgical replacement of their THA. The analysis of X-Rays showed a non significative decrease of periprosthetic bone resorption, predominant in proximal femoral area, and peripheral acetabular area. Concerning periprosthetic density, we observed a non statistically significative decrease of bone loss in all femoral area, and with predominance in proximal area. Conclusions: In this observational study, in patients with painful periprosthetic resorption of THA, Risedronate seems to have an effect on pain, with a significant decrease of walking pain, and a significant increase of walking distance. Only 28% needed replacement of prosthetic implant. A randomized study will be conducted to confirm these results. References: Sköldenberg, O.G., The effect of weekly risedronate on periprosthetic bone resorption following total hip arthroplasty. J Bone Joint Surg Am., 2011. 93: p. 1857-1864. Farrar, J.T., Clinical importance of changes in chronic pain intensity measured on an 11-point numerical pain rating scale. Pain, 2001. 94: p. 149-158. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5275